2019
DOI: 10.18502/jebhpme.v3i2.1223
|View full text |Cite
|
Sign up to set email alerts
|

Identifying executive challenges of performance-based payment from medical and educational hospitals managers’ perspective and offering solutions in Isfahan (2018)

Abstract: Introduction: Performance-based payment is a payment model that attempts to reward the measured dimensions of performance and encourages health service providers to achieve predetermined goals by financial incentives. This study aimed to identify executive challenges of performance-based payment from medical and educational hospitals managers’ perspective and offering solutions in Isfahan 2018. Methods: This study was a qualitative study. Semi structured interviews were used to collect data. The research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The sooner a plan is implemented without the right timing, the more likely it is to fail. [ 3 ] In a study conducted by Condo et al ., The findings showed that the development of a suitable platform in the implementation of the plan and the creation of the required capacities before the start of the plan is considered as an effective factor in the realization of the performance payment plan. [ 10 ]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The sooner a plan is implemented without the right timing, the more likely it is to fail. [ 3 ] In a study conducted by Condo et al ., The findings showed that the development of a suitable platform in the implementation of the plan and the creation of the required capacities before the start of the plan is considered as an effective factor in the realization of the performance payment plan. [ 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was mentioned that the lack of motivation in employees to implement a performance-based payment plan has led to employee resistance and failure of the plan. [ 3 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first large-scale PBP plan in the private sector was introduced by the Comprehensive Health Care Association in California in 2003 and still is active. Since then, PBP plans have been employed by strategic health purchasers in most of the countries in order to strengthen and reform traditional payment systems [ 6 ]. Nowadays, most organizations in charge of protecting health and Medicaid program resort to PBP plan.…”
Section: Introductionmentioning
confidence: 99%